A Novel Computed Tomography-Ultrasound Image Fusion Technique for Guiding the Percutaneous Kidney Access - Shen, Xiaobo; Li, Kaiwen; Wu, Zhenyu; Lu, Cheng; Yu, Hao; Lai, Cong; Tang, Zhuang; Li, Kuiqing; Xu, Kewei (Urology Journal, 2023)
Purpose: To describe the feasibility of computed tomography (CT)-ultrasound image fusion technique on guiding percutaneous kidney access in vitro and vivo. Materials and Methods: we compare CT-ultrasound image fusion technique and ultrasound for percutaneous kidney puncture guidance by using an in vitro pig kidney model. The fusion method, fusion time, ultrasound screening time, and success rate of puncture were compared between the groups. Next, patients with kidney stones in our hospital were randomized in the study of simulated puncture guidance. The general condition of patients, fusion method, fusion time, and ultrasound screening time were compared between the groups. Results: A total of 45 pig models were established, including 23 in the CT-ultrasound group and 22 in the ultrasound group. The ultrasound screening time in the CT-ultrasound group was significantly shorter than that in the ultrasound group (P < .001). In addition, the success rate of puncture in the CT-ultrasound group was significantly higher than that in the ultrasound group (P =.015). Furthermore, in the simulated PCNL puncture study, baseline data including age, BMI, and S.T.O.N.E score between the two groups showed no statistical difference. The ultrasound screening time of the two groups was (2.60 ± 0.33) min and (3.37 ± 0.51) min respectively, and the difference was statistically significant (P < .001). Conclusion: Our research revealed that the CT-ultrasound image fusion technique was a feasible and safe method to guide PCNL puncture. Compared with traditional ultrasound guidance, the CT-ultrasound image fusion technique can shorten the learning curve of PCNL puncture, improve the success rate of puncture, and shorten the ultrasound screening time.